Targeted energy transfer in a 2-DOF mechanical system coupled to a non-linear energy sink with varying stiffness. (September 2017) - Lamarque, Claude-Henri; Thouverez, F; Rozier, B; Dimitrijevic, Z
The dynamical behavior of a non-linear mechanical system with two degrees of freedom (DOFs) during free and forced excitations is studied analytically and numerically. The non-linearity of the system is represented intentionally by a smooth non-linear simple function with periodically varying stiffness around a constant value for the sake of practical investigations. Analysis of the system leads to a method that could be used to design the non-linear energy sink (NES) so that the behavior of the system during relaxation and its strongly modulated response (SMR) could be improved versus the constant stiffness configuration.